The Role of Artificial Intelligence in Incident Response for Digital Domain SMEs - Oluwawemimo, Esther (My University, 2024)
The rate of cybersecurity attacks on small to medium enterprises (SMEs) has been rapidly advancing in recent years. The use of artificial intelligence (AI) is one emerging technology that has grown significantly in the cybersecurity field and has great potential to combat the effects of cyberattacks by enabling more advanced and efficient incident response processes. AI-based incident response solutions can detect and respond to cybersecurity incidents by analysing large amounts of data and identifying suspicious patterns. This technology gives SMEs a security edge by automatically responding to incidents in real-time. This research study aims to analyse the role of artificial intelligence in incident response for digital domain SMEs. It also evaluates the maturity level of SMEs by measuring their overall security posture regarding the utilisation of AI in incident response. A survey questionnaire is the empirical method used to gather quantitative data systematically in this research study. 53 participants from various digital domain sectors with various years of work experience in cybersecurity made up the sample population pool for this study. The quantitative data were analysed using inferential statistics, with 6 major sections covering general information, cybersecurity awareness, incident response management, security controls and technology, current usage of AI, and experiences. The study's results show that organisations using AI in their incident response processes can detect and respond to incidents more quickly and at a faster rate than those not utilising AI. Three major areas of limitations in using AI affecting SMEs were indicated: lack of expertise, cost limitations, and difficulty integrating AI solutions with existing systems. This study concluded that a low percentage of SMEs are utilising AI in incident response. Participants provided recommendations regarding the implementation and impact of AI in incident response for SMEs
Keywords: Artificial intelligence, Incident response, Cybersecurity, SMEs